2013
DOI: 10.1186/1472-6882-13-10
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Improved glycemic control, pancreas protective and hepatoprotective effect by traditional poly-herbal formulation “Qurs Tabasheer” in streptozotocin induced diabetic rats

Abstract: BackgroundThe present study was undertaken to evaluate the antihyperglycemic, antihyperlipidemic and hepatoprotective effect of a traditional unani formulation “Qurs Tabasheer” in streptozotocin (STZ) induced diabetic wistar rats. Up till now no study was undertaken to appraise the efficacy of “Qurs Tabasheer” in the diabetic rats. Qurs Tabasheer is a unani formulation restraining preparations from five various herbs namely Tukhme Khurfa (Portulaca oleracea seed), Gule Surkh (Rosa damascena flower), Gulnar (Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
3
26
2
1
Order By: Relevance
“…56-58 GK regulates glucose uptake and glycogen synthesis and suppresses glucose production. [61][62][63] The present results show no changes in rats treated with pterostilbene, indicating that this enzyme was not involved in the beneficial effect of pterostilbene on glycaemic control. 59 In the present study the administration of pterostilbene to rats resulted in a significant increase in the activity of this enzyme in the PT15 group, but not in the PT30 group.…”
Section: Discussioncontrasting
confidence: 49%
“…56-58 GK regulates glucose uptake and glycogen synthesis and suppresses glucose production. [61][62][63] The present results show no changes in rats treated with pterostilbene, indicating that this enzyme was not involved in the beneficial effect of pterostilbene on glycaemic control. 59 In the present study the administration of pterostilbene to rats resulted in a significant increase in the activity of this enzyme in the PT15 group, but not in the PT30 group.…”
Section: Discussioncontrasting
confidence: 49%
“…All group rats received different doses of MM extract and glibenclamide using intragastric tube once daily for 28 days, continuously [15]. According to the acute toxicity testing of the MM extract, the different doses i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, two studies were discarded due to full-text unavailability. Detailed full-text examination of 24 remaining studies revealed that 18 did not meet inclusion criteria (Kemper et al, 2015, Krusche et al, 2013, Ljotsson et al, 2011, Murray et al, 2015, Zernicke et al, 2013), for example, Michel et al measured strain-based work-family conflict, but had no direct measure of perceived-stress (Michel et al, 2014). Scanning reference lists of the remaining six studies identified one additional eligible study (Wolever et al, 2012), with yet another identified by hand-searching contents pages from two journals (Mak et al, 2015).…”
Section: Evidence Synthesismentioning
confidence: 99%